IMPLEMENTASI COVID-19 STRATEGIC PREPAREDNESS AND RESPONSE PLAN (SPRP) DI INDONESIA YANG DI REKOMENDASIKAN OLEH WHO DALAM MENANGANI COVID-19 TAHUN 2020-2021 - Hafis, Ilham; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This study discusses the implementation of the COVID-19 Strategic Preparedness and Response Plan (SPRP) in Indonesia, which is recommended by the World Health Organization (WHO) in handling the COVID-19 pandemic in the period 2020-2021. The main objective of the study is to deeply analyze the effectiveness and impact of SPRP implementation at the national level. The research methodology involved an international health regime theory approach, which served as a foundation for understanding the global regulatory framework in response to the pandemic. Data collection was conducted through document analysis, government policies related to COVID-19, and WHO reports related to SPRP implementation in Indonesia. The results illustrate that the implementation of the SPRP in Indonesia involves mass vaccination strategies, the imposition of social restrictions, adjustments to risk-based vaccination strategies, and close coordination with WHO. In addition, the study highlighted health system strengthening efforts as a key component of the pandemic response. However, significant challenges such as equitable vaccine distribution and cross-sector coordination were identified as areas for improvement that need to be further investigated. The results showed that the SPRP vaccination program in Indonesia faced resistance and problems with vaccine supply. The government successfully approached religious leaders and the MUI to educate the public about the importance of vaccination. The procurement of vaccinations to meet the needs of the community was also successfully met through cooperation with institutions such as The Global Alliance for Vaccines and Immunizations (GAVI) in funding and distribution. The implementation of the strategic preparation and response plan has been tailored to the Indonesian context. Factors such as geographic diversity, demographics, and national health infrastructure have been taken into account in designing the response strategy. Keywords: SPRP, Covid-19 response, Indonesia, 2020-2021, WHO